The Existence of Paralegal in Minimizing Violence Against Women in Jembrana District - I Nyoman Gede Sugiartha; I Made Minggu Widyantara; Ni Kadek Erika; Putu Anggelita Putri; Kadek Darmayanti Putri (Community Service Journal of Law, 2022)
The role of paralegals in increasing public legal awareness has been widely studied. One of the important roles of paralegals in Bali, especially in the Jembrana Regency, is to minimize violence against women, which is still found in Bali, which is famous for upholding patrilineal lineages where there is an assumption that the position of men is higher than women. The aims of this research are to determine the increased awareness of the community in Tuwed Village, Melaya District, Jembrana Regency and understand about the protection of women in Tuwed Village, Melaya District, Jembrana Regency. The type of service carried out is empirical, so the type of writing approach is field data, which is used in this paper. Devotion is carried out by directly examining the spaciousness. The approach used is a case study approach. The result shows that The effectiveness of paralegals in preventing violence against women in Tuwed Village can be studied by linking the theory of Soerjono Soekanto, who argues that a law can be said to be effective if it meets five factors, namely, legal factors, law enforcement factors, facilities and facilities factors, factors society, and cultural factors. The role of paralegals in Tuwed Village can be said to be ineffective due to the lack of public knowledge about paralegals and lack of community knowledge related to violence against women, as well as constrained by factors of supporting facilities.